Feline fatale - Brown, Rita Mae; Brown, Sneaky Pie 1982- (New York Bantam Books, 2024)
"Spring flowers may be about to bloom in Crozet, Virginia, but Harry is thinking about snow. Her dear friend Ned Tucker is in the House of Delegates, advocating for a bill to improve road clearing during bad weather, and Harry and Ned's wife, Susan, have gone down to the statehouse to support him. Tensions are high between political parties, and no one can agree on anything for long enough to get something done. The bill's chief detractor is the glamorous Amanda Fields, a former newscaster turned delegate whose flair for the dramatic has earned her a formidable reputation--and made her more than a few enemies. Amanda's claws-out approach to politics might have some of her colleagues wishing she was dead, but the statehouse is rocked when one of the young pages who assists the delegates dies under mysterious circumstances. Could his death be related to the political infighting? Or is something even more sinister threatening the lives of Virginia's finest representatives? With help from her feline sidekicks, Mrs. Murphy and Pewter, as well as Tee Tucker the corgi and Irish Greyhound Pirate, Harry is determined to find the answers and restore order once more to the Capitol"--
"Rita Mae Brown & Sneaky Pie Brown" -- Dust jacket.
113751
Keywords: Haristeen, Harry (Fictitious character) -- Fiction; Murphy, Mrs. (Fictitious character) -- Fiction; Women detectives -- Virginia -- Fiction; Women cat owners -- Fiction; Murder -- Investigation -- Fiction; Fiction -- Mystery & Detective -- Cozy -- General; Cat owners -- Fiction; Virginia -- Fiction; Cozy mysteries; Political fiction; Novels; Romans